Satellite DNAs unveil clues about the ancestry and composition of B chromosomes in three grasshopper species - Milani, Diogo [UNESP]; Bardella, Vanessa B. [UNESP]; Ferretti, Ana B. S. M. [UNESP]; Palacios-Gimenez, Octavio M. [UNESP]; Melo, Adriana de S.; Moura, Rita C.; Loreto, Vilma; Song, Hojun; Cabral-De-Mello, Diogo C. [UNESP] (MDPI, 2018)
Supernumerary (B) chromosomes are dispensable genomic elements occurring frequently among grasshoppers. Most B chromosomes are enriched with repetitive DNAs, including satellite DNAs (satDNAs) that could be implicated in their evolution. Although studied in some species, the specific ancestry of B chromosomes is difficult to ascertain and it was determined in only a few examples. Here we used bioinformatics and cytogenetics to characterize the composition and putative ancestry of B chromosomes in three grasshopper species, Rhammatocerus brasiliensis, Schistocerca rubiginosa, and Xyleus discoideus angulatus. Using the RepeatExplorer pipeline we searched for the most abundant satDNAs in Illumina sequenced reads, and then we generated probes used in fluorescent in situ hybridization (FISH) to determine chromosomal position. We used this information to infer ancestry and the events that likely occurred at the origin of B chromosomes. We found twelve, nine, and eighteen satDNA families in the genomes of R. brasiliensis, S. rubiginosa, and X. d. angulatus, respectively. Some satDNAs revealed clustered organization on A and B chromosomes varying in number of sites and position along chromosomes. We did not find specific satDNA occurring in the B chromosome. The satDNAs shared among A and B chromosomes support the idea of putative intraspecific ancestry from small autosomes in the three species, i.e., pair S11 in R. brasiliensis, pair S9 in S. rubiginosa, and pair S10 in X. d. angulatus. The possibility of involvement of other chromosomal pairs in B chromosome origin is also hypothesized. Finally, we discussed particular aspects in composition, origin, and evolution of the B chromosome for each species.
Keywords: Fluorescent in situ hybridization; Orthoptera; Repeatexplorer; Satellite DNA; Supernumerary chromosome